Introskeletal erosion threat in mountain forests of the Czech Republic - S. Vacek; V.V. Podrázský; M. Mikeska; W.K. Moser (Journal of Forest Science, 2003)
Summarization of the potential of introskeletal erosion (ISE) was done on the basis of field surveys in the Šumava Mts., Krkonoše Mts. and Jeseníky Mts. areas. The results give a rough estimation of the ISE extent in mountain forests of the Czech Republic. They indicate that in the mountainous areas of the Czech Republic there are 46,535 ha of forest lands endangered by these processes, which represents 10.1% of mountain forests and 1.7% of the total forest area in the country. The worst situation is in the Krkonoše Mts., where the considerable ISE potential is on 30.5% of forest area (in the Jeseníky Mts. 16.6%, in the Novohradské hory Mts. 13.3%, in the Šumava Mts. 8.2%). Because these areas are relevant production and water protection areas, the ISE processes have to be studied carefully and forest lands have to be protected, also using special technologies for forest protection and restoration.